Pelatihan Pengenalan Augmented Reality sebagai Media Pembelajaran Bahasa Inggris pada Anak Usia Dini - Muhlisin Muhlisin; Syah Riza Octavy Sandy (Jurnal Pengabdian Masyarakat, 2026)
This community service programme is designed as an academic intervention to strengthen the professional capacity of early childhood teachers in integrating Augmented Reality (AR) learning technology into English vocabulary teaching. In the context of educational transformation in the era of Industry 4.0, mastery of pedagogical, content, and technological competencies in an integrated manner as outlined in the Technological Pedagogical and Content Knowledge (TPACK) framework has become a necessity. However, empirical evidence shows that most early childhood teachers still rely on conventional media and have not optimally utilised digital technology as a learning resource. This programme utilises a Participatory Action Research (PAR) approach that emphasises collaboration and continuous reflection through stages of needs analysis, intensive training, classroom implementation assistance, and practice-based evaluation. Teachers from the Yasmin Laboratory Early Childhood Education Centre at Muhammadiyah University in Jember were actively involved in the entire process as both subjects and partners in change. The results of the activities show a significant improvement in teachers' ability to design AR-based learning tools and implement them contextually. The use of AR flashcards not only enriches learning strategies but also increases engagement, motivation, and English vocabulary acquisition in early childhood. Thus, AR-based learning media can be positioned as a relevant pedagogical innovation in strengthening the quality of learning in early childhood education.